Accuracy of the surgeon's eye: Use of the tip–apex distance in clinical practice. Issue 7 (July 2015) - Wright, Jonathan; Kahane, Steven; Moeed, Abdul; MacDowell, Andrew
Abstract Tip–apex distance is a well described method for assessment of screw placement in dynamic hip screw fixation of proximal femoral fracture. A distance of <25 mm is associated with a significantly lower rate of cut out of the fixation device. Measurement is frequently performed retrospectively, although there has been no demonstration as to what accuracy the surgeon has of estimating tip–apex distance from image intensifier images, whilst scrubbed in theatre. Thirty-one clinicians working within orthopaedic departments were tested in their ability to identify adequacy of tip–apex distance on a series of image intensifier images. Level of seniority, awareness of the concept of tip–apex distance and use of the concept in clinical practice were each assessed. The accuracy in identifying the correct TAD was 82.5% in consultants, 83.8% in registrars and 71.1% in Senior house officers (SHO). The method was used in clinical practice by 50% of consultants, 89% of registrars and none of the SHOs.